The Role Of Internships In Building Students Professional Competencies (An Analysis Of The Internship Program At Bank BTN Mataram Main Branch) - Sudarta, Sudarta; Yunarni, Baiq Reinelda Tri; Fatabi, Rioni Citra; Yuliani, Rasmi; Indriani, Ria (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
In the era of globalization and increasing competition, professional competence has become a key factor determining individual success in the workforce. The internship program at Bank BTN serves as an effective means to develop students' professional competencies, encompassing the knowledge, skills, and attitudes necessary in a work context. Through practical experience, students not only acquire technical skills but also build character and a strong work ethic. This program encourages the development of interpersonal skills, such as communication and teamwork, which are essential in the workplace. Although students face challenges such as adapting to new work environments and pressure to meet expectations, this experience provides valuable learning opportunities. Therefore, collaboration between educational institutions and industries, including Bank BTN, is crucial to create optimal internship experiences that support the professional competency development of students.